Proceedings of the 18th International Workshop on Software and Compilers for Embedded Systems 2015
DOI: 10.1145/2764967.2764976
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-based Virus Detection on Heterogeneous Embedded Systems

Abstract: Embedded systems, e.g. in computer vision applications, are expected to provide significant amounts of computing power to process large data volumes. Many of these systems, such as used in medical diagnosis, are mobile devices and face significant challenges to provide sufficient performance while operating on a constrained energy budget.Modern embedded MPSoC platforms use heterogeneous CPU and GPU cores providing a large number of optimization parameters. This allows to find useful trade-offs between energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…We showed that pattern recognition can be performed within certain limits on mobile devices. We ported an image-based virus detection application [12] from a dedicated computer to a high performance embedded system by using approximation techniques.…”
Section: Contribution To Smart Systemsmentioning
confidence: 99%
“…We showed that pattern recognition can be performed within certain limits on mobile devices. We ported an image-based virus detection application [12] from a dedicated computer to a high performance embedded system by using approximation techniques.…”
Section: Contribution To Smart Systemsmentioning
confidence: 99%